Konflik Agraria dalam Perspektif HAM di Desa Namo Rube Julu Kec. Kutalimbaru - KIKI JULIANTI P SIREGAR (Politeia: Jurnal Ilmu Politik, 2013)
This study tried to describe the agrarian conflict that occurred in the village of Sei Mencirim and Namo Rube Julu, Kutalimbaru District, Kabupaten Deli Serdang. Where the purpose of this study is to discuss about any form of human rights violations that occurred in agrarian conflict in village of Sei Mencirim and Namo Rube Julu, Kutalimbaru District, Kab. Deli Serdang. Therefore, researcher used a case study design and method of interviews as the main data col-lection technique and the study relies on the analysis of interviews obtained and its relevance to the applicable laws and the theories used. The findings of this study, among others, there are three forms of human rights violations that occurred in the village of Namo Sei Mencirim and Rural Rube Julu. First, agricultural land owned by the people of widely plantations; Secondly, acts of violence experienced by farmers; Third, farmers do not receive the decent result of the production itself.Keywords: Conflict, human right, violence.